The Relationship Between Students’ Readiness, Bim Usage, Bim Adoption And Bim Adoption Level Among Malaysian Polytechnic Architecture Students - Azhar, Nurhidayah (2023)
Building Information Modelling, or BIM, is a collaborative system used in the building industry. However, BIM implementation in Malaysia Architecture Engineering Construction (AEC) industry is still low. The method for encouraging the AEC industry to use BIM is to prepare graduates with this technology expertise. This research aims to examine the status of BIM adoption among Malaysian polytechnic architecture students. The questions that this research explores are: what is the level of students’ readiness, BIM usage and BIM adoption level? In order to explore the questions, this research used the Technology Acceptance Model (TAM). The suggested model in particular, extends the TAM by adding students’ readiness as an external variable. A quantitative research with questionnaire survey was conducted to examine the hypotheses. The survey was distributed to fifth semester Malaysian polytechnic architecture students using stratified simple random sampling method. Responses were analysed using descriptive analysis, Pearson correlation, and multiple regression in Statistical Package for Social Science (SPSS) version 26. The results showed that students’ readiness, BIM usage, and BIM adoption level were high. Students’ adoption levels were in the high and moderate levels, with the majority of them at the manipulation level. Hypotheses one and two; students’ readiness and BIM usage significantly affected BIM adoption, hypothesis 3; BIM adoption has significantly affected BIM adoption level.